On Equality of Pay for Women and Men with Equal Qualifications - Willi Koll (Wirtschaftsdienst)
Abstract Pay inequality is a key element that prevents equal treatment of women and men. Even when known wage-relevant differences are excluded, there is still a wage gap, the adjusted gender pay gap. However, an increase of company employment costs due to women’s maternity leave may explain part of the adjusted gender pay gap. In order to compensate for this higher cost and to end discrimination in wages, some options are suggested.